Testicular localization and potential function of vimentin positive cells during spermatogonial differentiation stages - Tabar, Amirreza Niazi; Azizi, Hossein; Hashemi Karoii, Danial; Skutella, Thomas (Animals, 2022)
Vimentin is a type of intermediate filament (IF) and one of the first filaments expressed in spermatogenesis. Vimentin plays numerous roles, consisting of the determination of cell shape, differentiation, cell motility, the maintenance of cell junctions, intracellular trafficking, and assisting in keeping normal differentiating germ cell morphology. This study investigated the vimentin expression in two populations of undifferentiated and differentiated spermatogonia. We examined vimentin expression in vivo and in vitro by immunocytochemistry (ICC), immunohistochemistry (IMH), and Fluidigm real-time polymerase chain reaction. IMH data showed that the high vimentin expression was localized in the middle of seminiferous tubules, and low expression was in the basal membrane. ICC analysis of the colonies by isolated differentiated spermatogonia indicated the positive expression for the vimentin antibody, but vimentin’s expression level in the undifferentiated population was negative under in vitro conditions. Fluidigm real-time PCR analysis showed significant vimentin expression in differentiated spermatogonia compared to undifferentiated spermatogonia (p < 0.05). Our results showed that vimentin is upregulated in the differentiation stages of spermatogenesis, proving that vimentin is an intermediate filament with crucial roles in the differentiation stages of testicular germ cells. These results support the advanced investigations of the spermatogenic process, both in vitro and in vivo.
Gesehen am 22.03.2022